PENGARUH ACADEMIC PEER SUPPORT TERHADAP SCHOOL ENGAGEMENT PADA SISWA SMP “X” DI BANDUNG - Theresa Diana Putri Biantoro; Jane Savitri (Fakultas Psikologi Universitas Tarumanagara, 2023)
This study aims to determine the effect of the academic peer support dimension on school engagement at SMP